Book Notes [59, Spring 2007] - Finkel, Alvin (Labour / Le Travail, 2007)
The article reviews several books including the "Risky Business: Nuclear Power and Public Protest in Canada," by Michael D. Mehta," "Saskatchewan: The Roots of Discontent and Protest," by John W. Warnock, and "City of Clerks: Office and Sales Workers in Philadelphia 1870-1920," by Jerome P. Bjelopara.
Keywords: BJELOPARA, Jerome P.; BOOKS -- Reviews; CITY of Clerks: Office & Sales Workers in Philadelphia 1870-1920 (Book); MEHTA, Michael D.; Nonfiction; RISKY Business: Nuclear Power & Public Protest in Canada (Book); SASKATCHEWAN: The Roots of Discontent & Protest (Book); WARNOCK, John W.